Integrating Acceptance and Commitment Therapy With Functional Analytic Psychotherapy: A Case Study of an Adult Male With Mixed Depression and Anxiety. (February 2020) - Brem, Meagan J.; Coop Gordon, Kristina; Stuart, Gregory L.
Acceptance and commitment therapy (ACT) gained support for treating transdiagnostic features of major depressive (MDD) and generalized anxiety disorders (GAD). However, ACT's intrapersonal emphasis may be insufficient for targeting interpersonal treatment goals. Integrating ACT with functional analytic psychotherapy offers theory-based strategies for responding to ACT-specific processes through the contingent interpersonal relationship thereby targeting both intra- and interpersonal treatment goals. Yet, no research examined the efficacy of this integrative approach (i.e., functional-analytic acceptance and commitment therapy [FACT]) in treating comorbid MDD and GAD. In this case study, we conceptualized a man with comorbid MDD and GAD from a FACT perspective, described FACT treatment across 28 sessions, and presented pretreatment, termination, and 6-month posttreatment data on FACT-specific treatment targets. Depression symptoms, self-compassion, mindfulness, and interpersonal relationships improved despite unchanged physiological anxiety symptoms throughout treatment. These preliminary data provide clinicians with a conceptual framework for treating clients using FACT and may guide future research on integrative treatment approaches.